2021
DOI: 10.1016/j.omtm.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of blood-brain-barrier-penetrating AAV capsids by RNA-driven biopanning

Abstract: Therapeutic payload delivery to the central nervous system (CNS) remains a major challenge in gene therapy. Recent studies using function-driven evolution of adeno-associated virus (AAV) vectors have successfully identified engineered capsids with improved blood-brain barrier (BBB) penetration and CNS tropism in mouse. However, these strategies require transgenic animals and thus are limited to rodents. To address this issue, we developed a directed evolution approach based on recovery of capsid library RNA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 48 publications
4
103
0
Order By: Relevance
“…The corresponding AAV library was produced by co-transfection of the AAV5-NNK library plasmid with AdHelper and 3-stop plasmid in a way similar to that of previous studies. 31 , 32 We performed 2 rounds of in vivo screening and harvested the liver mRNA from the mice treated with the AAV5 variant library for next-generation sequencing (NGS) to obtain oligopeptide candidates. In the next step, each capsid candidate was distributed with a unique barcode in the cis -element plasmid encoding GFP as depicted in earlier studies 33 and packaged into a distinct AAV serotype with GFP transgene and the barcode ( Figure S1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding AAV library was produced by co-transfection of the AAV5-NNK library plasmid with AdHelper and 3-stop plasmid in a way similar to that of previous studies. 31 , 32 We performed 2 rounds of in vivo screening and harvested the liver mRNA from the mice treated with the AAV5 variant library for next-generation sequencing (NGS) to obtain oligopeptide candidates. In the next step, each capsid candidate was distributed with a unique barcode in the cis -element plasmid encoding GFP as depicted in earlier studies 33 and packaged into a distinct AAV serotype with GFP transgene and the barcode ( Figure S1 A).…”
Section: Resultsmentioning
confidence: 99%
“…These methods have been successful in developing novel AAV serotypes with more splendid tissue and organ tropisms toward the brain, skeletal muscle, and retina as compared with wild-type AAVs. 31 , 32 , 33 , 34 To generate novel AAV5 capsid mutants with better liver specificity while retaining low seroreactivity and NAb prevalence, we tried the above methods with minor modifications. After 2 rounds of library screening and another single round of barcode selection in mice, we picked up a candidate with a 7-mer oligopeptide “FAPTPGP” after the amino acid Q574 on the variable region VIII of the AAV5 capsid (referred to as AAVzk2 hereafter), which was demonstrated to have no negative impact on virus production.…”
Section: Introductionmentioning
confidence: 99%
“…AAV capsid-directed evolution strategies typically involve generating diverse capsid libraries followed by selection of variants with desired tropism in cell culture and/or animal models. This approach has generated modified vectors for augmented delivery to a number of tissues (Choudhury et al, 2016;Dalkara et al, 2013;Deverman et al, 2016;Kö rbelin et al, 2016;Li et al, 2016;Michelfelder et al, 2009;Nonnenmacher et al, 2020;Tse et al, 2017;Yang et al, 2009;Yang and Xiao, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The AAV9 variant AAV-PHP.B was the first variant to unlock efficient widespread gene transfer in adult mammals, traversing the BBB after systemic intravenous (IV) administration in mice 14 . Other variants have since followed with similar or enhanced properties, such as the ability to cross the BBB across different mouse strains, decreased transduction in non-CNS tissue, and biased tropism towards cell-types in the brain [15][16][17]22,23 . While two groups reported that the BBB-crossing tropism of AAV-PHP.B does not translate to the rhesus macaque 24,25 , studies reporting the systemic translatability of rodent neurotropic capsids in Old World primates are limited.…”
mentioning
confidence: 99%